Cobalt(II)-catalyzed electrophilic alkynylation of 1,3-dicarbonyl compounds to form polysubstituted furans via ?-? Activation - Roslan, Irwan Iskandar Bin (Wiley-VCH Verlag, 2016)
Advanced Synthesis and Catalysis